A Hybrid Model of Pediatric and Adult Critical Care During the Coronavirus Disease 2019 Surge: The Experience of Two Tertiary Hospitals in London and New York. Issue 2 (7th October 2020) - Deep, Akash; Knight, Philip; Kernie, Steven G.; D'Silva, Pam; Sobin, Brittany; Best, Thomas; Zorrilla, Maria; Carson, Lydia; Zoica, Bogdana; Ahn, Danielle
Abstract : Objectives: The current novel severe acute respiratory syndrome coronavirus 2 outbreak has caused an unprecedented demand on global adult critical care services. As adult patients have been disproportionately affected by the coronavirus disease 2019 pandemic, pediatric practitioners world-wide have stepped forward to support their adult colleagues. In general, standalone pediatric hospitals expanded their capacity to centralize pediatric critical care, decanting patients from other institutions. There are few units that ran a hybrid model, managing both adult and pediatric patients with the same PICU staff. In this report, we describe the hybrid model implemented at our respective institutions with shared experiences, pitfalls, challenges, and adjustments required in caring for both young and older patients. Design: Retrospective cohort study. Setting: Two PICUs in urban tertiary hospitals in London and New York. Patients: Adult and pediatric patients admitted to the PICU in roughly a 6-week period during the coronavirus disease 2019 surge. Interventions: None. Measurements and Main Results: The PICU at King's College Hospital admitted 23 non-coronavirus disease adult patients, while whereas the PICU at Morgan Stanley's Children Hospital in New York admitted 46 adults, 30 of whom were coronavirus disease positive. The median age of adult patients at King's College Hospital was higher than those admitted in New York, 53 years (19–77 yr) and 24.4 years (18–52 yr), respectively. Catering to the different physical, emotional, and social needs of both children and adults by the same PICU team was challenging. One important consideration in both locations was the continued care of patients with severe non-coronavirus disease–related illnesses such as neurosurgical emergencies, trauma, and septic shock. Furthermore, retention of critical specialists such as transplant services allowed for nine and four solid organ transplants to occur in London and New York, respectively. Conclusions: This hybrid model successfully allowed for the expansion into adult critical care while maintaining essential services for critically ill children. Simultaneous care of adults and children in the ICU can be sustained if healthcare professionals work collaboratively, show proactive insight into anticipated issues, and exhibit clear leadership.